The Occupation Pattern And Changes Among Tribes Of Banaskantha District: Gujarat (Journal of Namibian Studies : History Politics Culture, 2023)
This research study delves into the occupation patterns and livelihood sources of tribal households, with a primary focus on the Amirgadh and Danta regions in the Banaskantha district of Gujarat. The tribal population in these areas predominantly relies on traditional occupations related to agriculture and forest resources while leading nomadic lives in remote and isolated regions. The study seeks to explore the relationship between occupation and the livelihood levels of tribal communities, emphasizing the critical role of occupation in their development. The research adopts an explanatory approach and relies on primary data collected from 400 tribal households. Various statistical methods, including descriptive statistics, mean difference tests, and T-tests, are employed for data analysis. The findings reveal that agriculture and agricultural labour are the dominant occupations among tribal households in both Amirgadh and Danta. These traditional occupations yield relatively low economic returns, leading to an income-expenditure imbalance, which results in economic instability for indigenous families.